2019
DOI: 10.1590/0366-69132019653732441
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de biomaterial composto por hidroxiapatita e clorexidina para aplicação na cavidade oral

Abstract: ResumoA hidroxiapatita (HAp) está presente no organismo humano nos tecidos ósseos e dentários, em que do total da massa de cada tecido 30 a 70% correspondem a HAp, podendo ser aplicada como revestimentos de próteses ou até substituição de pequenas partes ósseas. Assim, o objetivo foi sintetizar HAp por precipitação, incorporar clorexidina (CHX) e avaliar as propriedades microbianas. A caracterização foi realizada por DRX, FTIR, TG/DTG, MET e MEV. A CHX foi incorporada à HAp por adsorção, variando a quantidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…The results were measured using the mean of the three inhibition zones, which were measured 24 h later without subtracting the diameter of the discs. The samples whose inhibition zones grew less than 10 mm were classified as inactive, while those whose halos varied from 10 to 15 mm were classified as active, and those with results above 15 mm were classified as highly active [29][30][31].…”
Section: Microbiological Analysis Methods Of Agar Disk Diffusion Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were measured using the mean of the three inhibition zones, which were measured 24 h later without subtracting the diameter of the discs. The samples whose inhibition zones grew less than 10 mm were classified as inactive, while those whose halos varied from 10 to 15 mm were classified as active, and those with results above 15 mm were classified as highly active [29][30][31].…”
Section: Microbiological Analysis Methods Of Agar Disk Diffusion Testmentioning
confidence: 99%
“…Its bactericidal effect results from the neutralization of the substrates of microorganisms present inside the root canals, with the continuous release of hydroxyl ions. Chlorhexidine at high concentrations is a bactericidal antimicrobial, but at lower concentrations, it becomes bacteriostatic [31,50]. It has been demonstrated that the application of chlorhexidine in root canals for 7 days brings significant results regarding the reduction of bacteria [51].…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Another band characteristic of the deformation of CH 2 groups was observed in the region of 1485 cm −1 . [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…A hidroxiapatita mineral existe naturalmente na forma de apatita de cálcio [Ca10(PO4)6(OH)2] e possui semelhança química com os componentes minerais dos ossos e dentes. Seu uso é largamente explorado em biomateriais como aplicações médicas, tais como revestimento de próteses e substituições de pequenas partes ósseas (DOS SANTOS et al, 2019).…”
Section: Introductionunclassified